2011
DOI: 10.1159/000333797
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Blockade with Rocuronium Bromide Increases the Tolerance of Acute Normovolemic Anemia in Anesthetized Pigs

Abstract: Background: The patient’s individual anemia tolerance is pivotal when blood transfusions become necessary, but are not feasible for some reason. To date, the effects of neuromuscular blockade (NMB) on anemia tolerance have not been investigated. Methods: 14 anesthetized and mechanically ventilated pigs were randomly assigned to the Roc group (3.78 mg/kg rocuronium bromide followed by continuous infusion of 1 mg/kg/min, n = 7) or to the Sal group (administration of the corresponding volume of normal saline, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Several authors found Hb crit at values between 1.6 and 3.0 g/dL [10,12,14-21]. In detail, Hb crit was reduced by 1) hypothermia (moderate reduction of body core temperature reduces total body O 2 demand [15]); 2) hyperoxemia (bioavailability of physically dissolved O 2 is excellent in profound anemia [12,16,17]); 3) infusion of norepinephrine (stabilization of coronary perfusion pressure during hemodilution [19]); 4) artificial O 2 carriers (maintenance of arterial oxygen content despite reduced hematocrit [18,22]), and 5) con-tinuous neuromuscular blockade (lowering skeletal muscular O 2 demand [23]).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors found Hb crit at values between 1.6 and 3.0 g/dL [10,12,14-21]. In detail, Hb crit was reduced by 1) hypothermia (moderate reduction of body core temperature reduces total body O 2 demand [15]); 2) hyperoxemia (bioavailability of physically dissolved O 2 is excellent in profound anemia [12,16,17]); 3) infusion of norepinephrine (stabilization of coronary perfusion pressure during hemodilution [19]); 4) artificial O 2 carriers (maintenance of arterial oxygen content despite reduced hematocrit [18,22]), and 5) con-tinuous neuromuscular blockade (lowering skeletal muscular O 2 demand [23]).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a reduction of Hb crit could be achieved by hypothermia (moderate reduction of body core temperature reduces total body O 2 demand [18]), infusion of norepinephrine (stabilization of CPP during hemodilution [19]), infusion of artificial O 2 carriers (maintenance of CaO 2 despite reduced hematocrit [20,21]) and continuous NMB (lowering skeletal muscular O 2 demand [22]). …”
Section: Discussionmentioning
confidence: 99%
“…In anesthetized pigs, cellular signs of hypoxia in the kidney and skeletal muscle developed at significantly higher Hb concentrations than in the heart, brain, and liver [17]. Last but not least, anesthetic measures such as deep neuromuscular blockade [18], application of norepinephrine to treat severe arterial hypotension [19], and induction of hypothermia [20] can increase anemia tolerance. From a physiologic point of view, anemia tolerance thus is quite remarkable.…”
Section: Physiology Of Progressive Anemiamentioning
confidence: 99%